Implementation of an Online Multimedia Pediatric Tracheostomy Care Module for Healthcare Providers. (18th January 2021) - Ahmed, Sadia T.; Yang, Catherina; Deng, Junwen; Bottalico, Danielle M.; Matta‐Arroyo, Esther; Cassel‐Choudhury, Gina; Yang, Christina J.
Abstract : Objectives/Hypothesis: To investigate the effect of a multimedia educational module on provider attitudes toward pediatric tracheostomy care. We also describe the process of module development and dissemination at an academic children's hospital. Study Design: Prospective observational study. Methods: The pediatric airway committee at an urban tertiary care center developed a multimedia pediatric tracheostomy care module. Nurses, respiratory therapists, as well as resident, fellow, and attending physicians caring for pediatric patients with tracheostomies were eligible. Managers and clinical supervisors from various units recruited participants to complete the pediatric tracheostomy care electronic module and pre‐ and postassessment knowledge quizzes and surveys. Provider confidence was analyzed using Kruskal–Wallis H ‐test and Mann–Whitney U ‐test, and paired t ‐test was used to compare pre‐ and postmodule quiz scores. Results: A total of 422 participants completed the module. A total of 275 participants completed the premodule survey, 385 completed the premodule quiz, 253 completed the postmodule survey, and 233 completed the postmodule quiz. Participants included providers in the neonatal intensive care unit, pediatric intensive care unit, pediatric emergency department, and pediatric wards. Postmodule surveys demonstrated a significant reduction in the average percentage of participants indicating lack of confidence with regards to changing an established tracheostomy, responding to accidental decannulation of established tracheostomy, and responding to accidental decannulation of fresh tracheostomy ( P < .001). Average quiz scores increased by 5.6 points from 83.0% to 88.6% ( P < .00001). Conclusions: A multimedia educational module can improve provider perception of their knowledge and confidence surrounding pediatric tracheostomy management. Level of Evidence: 3 Laryngoscope, 131:1893–1901, 2021